A Robust Approach to Risk Aversion - Antoine Bommier; François Le Grand (ETH Zurich, CER-ETH - Center of Economic Research, 2013)
We investigate whether the set of Kreps and Porteus (1978) preferences include classes of preferences that are stationary, monotonic and well-ordered in terms of risk aversion. We prove that the class of preferences introduced by Hansen and Sargent (1995) in their robustness analysis is the only one that fulfills these properties. The paper therefore suggests a shift from the traditional approach to studying the role of risk aversion in recursive problems. We also provide applications, in which we discuss the impact of risk aversion on asset pricing and risk sharing.
Keywords: E2; E43; E44; 330; risk aversion; recursive utility; robustness; ordinal dominance; risk free rate; equity premium; risk sharing; Risikoaversion; Entscheidung unter Risiko; Risikoprämie; Modellierung; Robustes Verfahren; Theorie